Effect of dietary lipid level on protein utilization and the size and proximate composition of body compartments of Colossoma macropomum (Cuvier) - van der Meer, M B (1997)
Juvenile Colossoma macropomum were fed ad libitum diets containing either 30% or 40% protein, while the dietary lipid level varied between 5% and 20%. Growth and protein utilization efficiency increased with the dietary lipid level. However, the economic feasibility of the addition of extra dietary lipid to C. macropomum diets is questionable, as for every extra gram of protein deposition it was necessary to replace 20-25 g of dietary carbohydrates by lipids. Moreover, increased dietary lipid levels resulted in increased lipid deposition. In C. macropomum, feed uptake was regulated by the dietary protein level and unaffected by the dietary lipid level. Dissection of the body into head, viscera and trunk revealed that 45-48% of the body lipids were stored in the trunk, independent of diet composition. A positive relation between dietary and body protein level was confirmed in this experiment. However, the dissection of the body revealed that the body protein concentrations in head -I- viscera and trunk are not changed significantly by the dietary protein level. The higher protein contents offish fed higher-protein diets are due to an increase in the relative weight of the trunk (muscle) to the total body weight.